MATERNAL PARTICIPATION IN THE PROVISION OF COMPLETE BASIC IMMUNIZATION IN LAMLAGANG VILLAGE, BANDAR RAYA SUBDISTRICT, BANDA ACEH CITY - Elvin, Putri Revani; Fajriana, Eulisa; Khairunnisa, Nova (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Complete basic immunization is essential for preventing infectious diseases in infants. However, the immunization coverage in the working area of Puskesmas Bandar Raya remains low (9.5%) compared to the Universal Child Immunization (UCI) target of 80%. This study aims to identify factors influencing maternal participation in providing complete basic immunization for children aged 12–24 months in Lamlagang Village, Banda Raya Subdistrict, Banda Aceh City. Method: This study employed a cross-sectional design with a total population of 32 respondents. Data were collected through interviews using a structured questionnaire and analyzed using the chi-square test. Result: The findings showed no significant relationship between maternal participation and variables such as age, education, occupation, availability of health facilities, and distance to health services. However, there were significant relationships with maternal knowledge (p=0.002), family support (p=0.003), and the role of health workers (p=0.001). Recommendation: The community health center (Puskesmas) is encouraged to conduct home visits and provide education to mothers to improve the coverage of complete basic immunization.